Development of an Effective Nonchemical Method against Plasmodiophora brassicae on Chinese Cabbage - Yu Gao; Guanghui Xu (International Journal of Agronomy)
Clubroot disease, caused by Plasmodiophora brassicae, is a serious soil-borne disease of crucifer worldwide, and it can significantly reduce yield and quality. Although some agrochemicals have been used to manage clubroot and can provide effective control, increasing use of chemical inputs causes several negative effects. In this study, using Chinese cabbage (Brassica rapa L. subsp. chinensis) as the test crop, we developed an effective nonchemical method that would protect the roots against P. brassicae infection by using a combination heat treatment and a cocktail of biocontrol agents. The data showed that this method could cause 91.7% inhibition of P. brassicae infection. The average height of plants (13.5 cm) using this method was about twice higher than that in control group (6.7 cm), and the average plant weight (3.19 g) was about three times increased compared to that in control set (1.23 g).